Difficulty analysis of biology education students in learning microteaching at Universitas Labuhanbatu - Delvi Rukmana Putri; Risma Delima Harahap; Sakinah Ubudiyah Siregar (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Education is a field that is very important for the future and influences other fields. One of the functions of education is to develop skills and abilities and form a better sense of dignity in the context of educating the life of the nation. This study aims to be able to see and know the difficulties faced by biology education students in microteaching lessons at Labuhanbatu University. The method used in this research is descriptive-qualitative. The sample in this study was made up of all fifth-semester biology education students. Data collection techniques included questionnaires and interviews. The results of the research that has been carried out regarding the analysis of the difficulties of biology education students in microteaching learning at Labuhanbatu University are: use of learning methods (42.61%), mastery of material (42.15%), skills in teaching (52.67%), skills in opening learning (54.36%), readiness in learning (54.70%), skills to ask (46.79%), skills to close learning (50.81%), and skills to explain (40.81%). Microteaching is very important for students in preparing themselves as prospective teachers and adding insight and knowledge.Abstrak Pendidikan merupakan suatu bidang yang sangat penting bagi masa depan untuk mengembangkan keahlian dan kemampuan serta membentuk generasi yang lebih baik dalam rangka mencerdaskan kehidupan bangsa. Penelitian ini bertujuan untuk dapat melihat serta mengetahui kesulitan yang dihadapi mahasiswa pendidikan biologi dalam pembelajaran microteaching di Universitas Labuhanbatu. Metode yang digunakan dalam penelitian ini yaitu kualitatif deskriptif. Sampel dalam penelitian ini yaitu seluruh mahasiswa pendidikan biologi semester lima, tehnik pengumpulan data berupa angket dan wawancara. Adapun hasil penelitian yang telah dilakukan mengenai analisis kesulitan mahasiswa pendidikan biologi dalam pembelajaran microteaching di Universitas Labuhanbatu yaitu: penggunaan metode pembelajaran (42.61%), penguasaan materi (42.15%), keterampilan dalam mengajar (52.67%), keterampilan dalam membuka pembelajaran (54.36%), kesiapan dalam pembelajaran (54.70%), keterampilan bertanya (47.69%), keterampilan menutup pembelajaran (50.81%), dan keterampilan menjelaskan (40.81%). Pembelajaran microteaching sangat penting bagi mahasiswa dalam mempersiapkan diri sebagai calon guru dan menambah wawasan dan pengentahuan.